Tiruvatikai Maṉavācakaṅkaṭanta Tēvanāyaṉār iyaṟṟiya Uṇmai viḷakkam - Nallaswami Pillai, J. M., 1864-1920; Vacciravēl Mutaliyār, Ka., 1906- (Yā. Kū. Ta. Nū. Pa. Vi. Ka. veḷiyīṭu ;, 1971)
Verse work of the Saivasiddhanta school of Hindu philosophy; with Tamil interpretive notes and English translation.